The Chinese Translation Study of the Cognitive Reserve Index Questionnaire - Cao, Ting; Zhang, Shifang; Yu, Mingming; Zhao, Xiaoyan; Wan, Qiaoqin (Frontiers in Psychology, 2022)
Purpose The purpose of this study was to perform the translation and adaption of the Cognitive Reserve Index questionnaire into Chinese and assess the reliability of the Chinese version. Materials and Methods The Chinese version of the Cognitive Reserve Index questionnaire was created from a standard forward-backward translation. A total of 371 volunteers, aged between 20 and 89 years, participated in this survey. Participants were divided into three age-groups (Young, Middle-aged, and Elderly), and subgroup differences were examined by independent samples t-tests, ANOVA analysis as well as post-hoc analysis. Pearson correlation analysis was applied to test the association between the total scores and each subscore (CRI-Education, CRI-WorkingActivity, and CRI-LeisureTime). The internal consistency and test-retest reliability of the Cognitive Reserve Index questionnaire were assessed. The test-retest reliability was measured among 40 participants with a 2-week interval using intraclass correlation coefficient. Results Strong correlations were observed between the total scores and each subscore (CRI-Education, CRI-WorkingActivity, and CRI-LeisureTime: r = 0.65, 0.79, and 0.70, respectively). In contrast, it was found low to moderate correlations among three subscores. The internal consistency was acceptable (Cronbach's alpha coefficient = 0.68). The intraclass correlation coefficient for total scores of the Chinese version of the Cognitive Reserve Index questionnaire was 0.87 (95% CI 0.74–0.93). Conclusion The Chinese version of the Cognitive Reserve Index questionnaire was a potentially reliable and practical tool for evaluating cognitive reserve accumulated through a person's life span.